Poetry as Memoir: Toi Derricotte’s Natural Birth and Redefining Motherhood - Willey, Nicole L. (Journal of the Motherhood Initiative for Research and Community Involvement, 2016)
Toi Derricotte’s Natural Birth (1983) is a powerful narrative poem hybrid that encapsulates the experience of her pregnancy and the birth of her son, who is almost grown when she finally writes the story. Scholars may not immediately think of this work as a motherhood memoir because of its genre, but it is just that. The fact that it is poetry does not take away from its validity as motherhood memoir, and, in fact, the ambiguity of the pain and beauty of this birth is better served through her lyrical narrative. Birth shares a story with its audience, which enlarges the universality of the experience of motherhood while bringing African feminist principles to the table. This work explores both adaptation (and redefinition) and networking (through collectivism and othermothering) as potential sites for power. Even more than the call for collectivism, this narrative poem is engaged in the work of redefining motherhood. Although the institution of motherhood sometimes oppresses women, it is still true that women have experienced and enacted positive change through mothering outside of the institution—either by choice or necessity. Mothering is hard no matter the circumstances. Derricotte must overcome many obstacles related to her subject position of a poor, Black mother, who often makes choices and shares truths that fall outside of the accepted mainstream logic for “good” parenting. In her honest portrayal, in her ambivalence, anger and fierce love, she has created new models for every mother.